Resource Allocation and Leveling in Fuel Cell Project Scheduling - Chang, Li Zu; Cheni, Lee Hu (International journal of industrial engineering and operational research, 2023)
In recent years, fuel cell technology has gained significant attention as an alternative energy source. Efficient project scheduling and appropriate resource allocation are crucial factors for successful Fuel Cell Project implementation. This paper aims to analyze and propose effective resource allocation strategies for Fuel Cell Project Scheduling. The study provides a comprehensive review of relevant literature, outlines the methodology adopted, presents numerical results, and concludes with recommendations for optimizing resource allocation in fuel cell projects. Finally, resource leveling plays a crucial role in ensuring the efficient and effective scheduling of projects. In the context of fuel cell project management, Microsoft Project provides a powerful toolset for optimizing resource allocation, addressing conflicts, and creating a balanced project schedule. By utilizing the resource leveling feature, project managers can allocate resources in a way that minimizes over-utilization or under-utilization, enhancing project efficiency and timely completion.